Treatment of acute traumatic nasopharyngeal stenosis with balloon dilation in two dogs. Issue 5 (3rd September 2022) - Ball, E; Chase, D; Coomer, A
ABSTRACT: Case history: Two dogs were referred to Veterinary Specialists Aotearoa for evaluation and treatment after sustaining significant head trauma. Case 1 was a 7-month-old, female Staffordshire Bull Terrier who was hit by a car at low speed. Case 2 was a 2-year old, male neutered German Shepherd who sustained a gunshot wound to the head whilst on duty for the New Zealand Police Dog Unit. Clinical findings: The dog in Case 1 suffered numerous facial fractures which caused collapse of the ventral nasal meatus and dorsal nasopharyngeal wall. The dog in Case 2 had extensive osseous and soft tissue damage to the nose, nasopharynx and cervical region with severe narrowing of the ventral meatuses, nasopharyngeal meatus and rostral nasopharynx due to multiple fracture fragments and shrapnel pieces. A diagnosis of traumatic nasopharyngeal stenosis was made in each case by computed tomography. Mechanical balloon dilation was used to treat the stenosis in both dogs. The balloon dilations were performed using a 12-mm balloon dilation catheter inserted in an antegrade fashion. In the first dog, the procedure was performed blind and was repeated three times with 5- and 9-day intervals between dilations. In the second dog, the procedure was performed under endoscopic guidance and again, was repeated three times with a 7-day interval between dilations. Clinical success was reported in both patients following treatment and the second dog also underwent a follow-up computed tomography scan which confirmed resolution of the stenosis. Diagnosis: Traumatic nasopharyngeal stenosis that was successfully treated with balloon dilation. Clinical relevance: Findings suggest that balloon dilation may be an effective technique for the treatment of traumatic nasopharyngeal stenosis in dogs. Multiple dilation procedures are likely required, but the procedure can ultimately result in long term clinical resolution. Abbreviations: CT: Computed tomography; VSA: Veterinary Specialists Aotearoa